The concept of moral education for Singaporean Muslim children: An analysis of Abdullah Nashih 'Ulwan's educational thought - bin Rabani, Mohamad Azmi (Program Studi Magister Pendidikan Agama Islam, 2024)
Morals are the main problem that is being felt in the world of Islamic education today. It has an impact on social, cultural, political, economic, and even religious problems in a country. Singapore's Muslim community is generally a Malay nation that also experiences the same problems as those experienced by the general Islamic community in various other parts of the world. Some cases of delinquency among Muslim children are caused by the destruction of their morals. In this case, the concepts of moral education that are extracted from the sources of Islam itself, namely the Qur'an and Hadith, are needed so that Singaporean Muslim children can continue to grow and develop in Islamic values. This article tries to analyze the concept of educational thought of Abdullah Nashih 'Ulwan, an Islamic education figure who consistently uses the two main sources of Islam in explaining moral education that can be applied to Muslim children in Singapore. The research used is library research using a descriptive-qualitative approach. Data analysis uses descriptive analysis, content analysis, and interpretative methods. The results show that one of the objectives of Islamic education in Singapore is to shape the morals of madrasa students to be in accordance with Islamic morals. This goal will be even stronger if we take the concept of moral education according to 'Ulwan. The concept aims to form children who believe, obey worship, and have good social sensitivity. The material is divided into three categories: moral education for Allah, moral education for oneself, and moral education for others. The education process has two supporters, namely teachers and parents as implementers, as well as appropriate methods, namely educating by example, habituation, advice, attention or supervision, and punishment. The evaluation is to see the extent of the achievements that have been obtained by children in preparing their morals, intellect, and mentality, shaping their physique, behavior, and social sense, and being able to become useful members of society. Abstrak Akhlak menjadi masalah utama yang sedang dirasakan oleh dunia pendidikan Islam saat ini. Hal itu berdampak pada permasalahan sosial, budaya, politik, ekonomi, bahkan agama di sebuah negara. Masyarakat muslim Singapura umumnya adalah berbangsa Melayu yang juga mengalami permasalahan yang sama sebagaimana yang dialami oleh umumnya masyarakat Islam di berbagai belahan dunia lainnya. Beberapa kasus kenakalan anak muslim disebabkan oleh rusaknya akhlak dan moral mereka. Dalam hal ini dibutuhkan konsep-konsep pendidikan akhlak yang digali dari sumber Islam itu sendiri, yaitu al-Qur’an dan Hadis, agar anak-anak muslim Singapura dapat terus tumbuh dan berkembang dalam nilai-nilai Islami. Artikel ini mencoba untuk menganalisis konsep pemikiran pendidikan Abdullah Nashih ‘Ulwan, tokoh pendidikan Islam yang konsisten menggunakan kedua sumber utama Islam tersebut, dalam menjelaskan pendidikan akhlak yang bisa diterapkan untuk anak muslim di Singapura. Penelitian yang digunakan adalah penelitian pustaka dengan menggunakan pendekatan kualitatif deskriptif. Analisis data menggunakan analisis deskriptif, analisis isi, dan metode interpretatif. Hasil penelitian memperlihatkan bahwa salah satu tujuan pendidikan Islam di Singapura memiliki tujuan untuk membentuk akhlak para siswa madrasah agar sesuai dengan akhlak Islam. Tujuan ini akan semakin kuat jika mengambil konsep pendidikan akhlak menurut ‘Ulwan. Konsep tersebut memiliki tujuan untuk membentuk anak yang beriman, taat beribadah, dan memiliki kepekaan sosial yang baik. Materinya terbagi menjadi tiga, yaitu pendidikan akhlak kepada Allah, pendidikan akhlak kepada diri sendiri, dan pendidikan akhlak kepada orang lain. Proses pendidikannya memiliki dua pendukung, yaitu guru dan orang tua sebagai pelaksana, serta metode yang tepat, yaitu mendidik dengan keteladanan, pembiasaan, nasihat, perhatian/ pengawasan, dan hukuman. Adapun evaluasinya adalah melihat sejauh mana pencapaian yang telah diperoleh anak dalam mempersiapkan akhlaknya, intelektualnya, mentalitasnya, dan juga membentuk fisiknya, perilakunya, dan rasa sosialnya, serta mampu menjadi anggota masyarakat yang bermanfaat.